PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KABUPATEN BENGKALIS - Suharyono Suharyono (Inovbiz: Jurnal Inovasi Bisnis, 2019)
Tax is one of the sources of financing for national development in order to improve society. Taxes have a very important role to play in state revenues in the present, This happens because taxes are a sure source of contribution to the country. In this regard, the importance of managing tax is a priority for the government. There are various types of taxes imposed on the public, one of which is the Land and Building Tax. This study aims to determine the effect of taxpayer awareness and tax knowledge on taxpayer compliance in paying land and building tax in the city of Bengkalis. The sample in this study were 347 taxpayers in the city of Bengkalis. The sample collection technique used in this study was using non probability sampling by convenience sampling method. The types of data used in this study are quantitative data in the form of values or scores on the answers given by respondents to the questions in the questionnaire. The data source used is primary data. Primary data obtained from direct observation, interviews, questionnaires and observations. The method of data analysis uses the test of validity and reliability test, classic assumption test, multiple regression analysis. Based on the results of the research that has been done, it can be concluded that there is a significant positive influence between the awareness of taxpayers and knowledge of taxation on taxpayer compliance in paying land and building tax.